Turkmenistan : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper reviews economic developments in Turkmenistan during 1994-97. To address the growing economic difficulties, the government announced an economic reform package for 1996, which aimed at achieving a recovery in output, sharply lowering inflation, maintaining a strong reserve position, and promoting private sector development. The reform package had mixed success. Monetary and credit policy was generally restrained until late 1996, contributing to a moderation in inflation. However, economy-wide public sector wages were doubled in October, against a background of continued payment difficulties in the gas sector and a decline in GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet